God's Consistency Which Is Promised Through a New-Normal-Era Health Protocol in Order to Preserve The Essence Of Humanity - Lister Napitupulu (Sekolah Tinggi Teologi Simpson, 2021)
Health anthropology has experienced a tremendous new revolution, started from last year, 2020. A New-normal Health Protocol formulation was put in place to deal with the Covid-19 pandemic outbreak. Natural and social media communities complained about humanity and human rights degradation, raising calls for resistance due to imposed global restrictive regulations. God in Christian theology is a God who promises to His human creation that He will be with and help humans to have a happy and prosperous life. By doing literature research, this paper tries to explore whether the Covid-19 management guidelines are by the consistency of covenant God in restoring the essence of humanity. How is the relation between two paradigms of society, from God’s side and human’s side, through the Health Protocol intervention? The finding is that God, who created perfect human beings, keeps all the processes of his life to become the people of His eternal kingdom. Society and individuals should be able to respond to global regulations as support for faith and perspective to continue to live and fill the days ahead with the maximum quality of life as prime human beings. ABSTRAK: Antropologi kesehatan mengalami suatu revolusi baru yang dahsyat, dimulai dari tahun lalu, 2020. Sebuah rumusan Protokol Kesehatan New-normal diberlakukan untuk menangani wabah pandemi Covid-19. Masyarakat nyata dan media sosial mengeluhkan perasaan degradasi kemanusiaan dan hak asasi manusia bahkan mencuatkan seruan perlawanan karena peraturan pembatasan global yang dipaksakan. Allah dalam teologi Kristen adalah Allah yang berjanji kepada manusia ciptaan-Nya bahwa Ia akan menyertai dan menolong manusia untuk mendapatkan kehidupan yang sejahtera dan berbahagia. Dengan melakukan sebuah literature-research tulisan ini mencoba menelusuri apakah pedoman tatalaksana Covid-19 ini sesuai dengan konsistensi Allah yang berjanji dalam hal memulihkan esensi kemanusiaan. Bagaimanakah hubungan antara dua paradigma tentang kemanusiaan dari sisi Allah dan manusia melalui intervensi Protokol Kesehatan. Temuan bahwa Allah yang menciptakan manusia yang sempurna menjaga sepanjang proses kehidupannya agar menjadi umat kerajaan kekal-Nya. Seyogyanya masyarakat dan individu dapat menyikapi peraturan global sebagai penopang iman dan cara pandang sehingga tetap dapat menjalani dan mengisi hari-hari ke depan dengan kualitas hidup maksimal sebagai manusia prima.